ANALISIS PENERAPAN SISTEM DAN PROSEDUR PEMBERIAN KREDIT PEMILIKAN RUMAH (KPR) SUBSIDI PADA BANK TABUNGAN NEGARA CABANG MANADO - Takalamingan, Hibatullah Fauzan; Saerang, David P. E.; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2018)
This study aims to find out how the System and Procedure of the Subsidy House Ownership Credit (KPR) in Manado Branch of PT. Bank Tabungan Negara. This type of research is descriptive with qualitative approach. The data collecting techniques done were interview, observation and documentation. The steps taken to analyze the acquired data were done in two phases, they were (1) analyzing how the System and Procedure of the Subsidy House Ownership Credit (KPR) in Mandao Branch of PT. Bank Tabungan Negara (BTN) is already good, and (2) analyzing whether the factors that cause bad credit in the House Ownership Credit (KPR) in Manado Branch of PT. Bank Tabungan Negara and how the settlement of bad credit is done by the Manado Branch of PT. Bank Tabungan Negara. The result of the research showed that the Subsidy House Ownership Credit (KPR) System and Procedure were good and was suitable with the standards applied by the government. Factors that cause bad credit in the House Ownership Credit (KPR) System and Procedure in Manado Branch of PT. Bank Tabungan Negara were ill debtors, the debtor has no job, the house is not standard, and the character of the debtor. The settlement effort is to collect and if it cannot be billed then a decision is taken by auction.Keywords: System and Procedure, the Subsidy House Ownership Credit, and Bad Credit